Sea blue histiocytosis: a common abnormality of the bone marrow in myelodysplastic syndromes. Issue 11 (November 1993) - Howard, M R; Kesteven, P J
Abstract : AIMS--To determine whether myelodysplastic syndromes (MDS) are associated with sea blue histiocytosis in the bone marrow. METHODS--A retrospective review of bone marrow aspirates from 35 patients presenting consecutively with MDS and from 20 patients with each of the following: normal marrow appearance (routine staging for non-Hodgkin's lymphoma), polycythaemia rubra vera, immune thrombocytopenic purpura (ITP), chronic myeloid leukaemia (CML) in chronic phase. RESULTS--Sea blue histiocytes were present in the marrow in 12 of 35 cases of MDS and occurred in large numbers in three of these cases. Sea blue histiocytes varied in the degree of cytoplasmic granularity and some cells were intermediate in appearance between classic sea blue histiocytes and pseudo-Gaucher cells. Sea blue histiocyte granules additionally stained positively with Sudan black and periodic acid schiff. Sea blue histiocytes occurred only in the presence of marrow hypercellularity. Their presence did not correlate with FAB subtype, degree of dyserythropoeisis, or megakaryocyte numbers. No sea blue histiocytes were found in the normal marrow or polycythaemia cases. In ITP sea blue histiocytes were seen in two of 20 cases and in chronic myeloid leukaemia in eight of 20 cases. CONCLUSIONS--Sea blue histiocytes are a common cytological feature in the bone marrow of patients with MDS. As other disorders frequently associated with marrow sea blue histiocytes are relatively rare MDS is probably the most common cause of this phenomenon in a northern European population.